Model Pengelolaan Kualitas Air Sungai Citarum - Nurdiyanto Nurdiyanto (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2015)
ABSTRAKKualitas air Sungai Citarum dinilai sudah tidak sesuai dengan Baku Mutu Air. Kctidaklayakan air Sungai Citarum tcrscbut dipastikan akibat tingginya tingkat penccmaran. Sclain linibah industri, penyumbang pencemaran tertinggi berasal dari limbah domestik. Hal tersebut terlihat dari kandungan bakteri koli tinja atau Escherichia Coli (E. Coli) di Sungai Citarum. Kondisi kualitas air Sungai Citarum ditinjau dari E. Coli memperlihatkan kecenderungan naik di Kecamatan Dayeuhkolot Kabupaten Bandung. Selain kadar E. Coli, Biological Oxygen Demand (BOD) dan Chemical Oxygen Demand (COD) di Sungai Citarum juga kadamya tinggi. Tingginya angka BOD mengindikasikan banyak limbah organik yang terkandung dalam sumber air tersebut.Scbagai upaya penanggulangan secara scdcrhana, harus dibangun septic tank untuk setiap perumahan atau septic tank komunal di permukiman padat penduduk secara kolektif. Perlu dilakukan revitalisasi pengolahan limbah industri dan ketegasan aparat pemerintah dalam melakukan pengawasan terhadap perusahaan saat mengolah limbahnya, terutama membuat instalasi pengolahan air limbah (1PAL).Kata Kunci : Escherichia Coli (E. Coli), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Instalasi Pengolahan Air Limbah (IPAL).ABSTRACTWater quality CRB is considered to be not in accordance with the Water Quality Standard. The inadequacy of water CRB ascertained due to high levels of pollution. In addition to industrial waste, the highest contributor to the pollution comes from domestic waste. It is seen from the content of fecal colifonns bacteria or Escherichia Coli (E. Coli) in the CRB. CRB water quality conditions in terms oJ'E. coli showed an upward trend in the District Dayeuhkolot Bandung regency. In addition to the levels of E. Coli. Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) The CRB also high levels. The high number of BOD indicates a lot of organic waste contained in the water source.As a simple reduction efforts, should be built septic tanks for each residential or communal septic tanks in densely populated settlements collectively. Need to revitalize industrial waste processing and f irmness of government officials in monitoring the company when processing the waste, mainly making wastewater treatment plant (WWTP).Keywords: Escherichia Coli (E. Coli), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Waste Water Treatment Plant (WWTP).Â